Process of recovery from co-dependency among wives of drug addicts in Nar-anon self-help groups in Iran - Askian, Parastoo (2015)
Drug addiction adversely affects the addict and his/her entire family. Spouses of drug addicts are seriously affected by their partners’ addiction. Co-dependency is usually attributed to family members of addicts, especially spouses. It is often described as a condition whereby a person/s related to the drug addict is extremely focused on the addict and his/her behavior such that the family member eventually becomes dysfunctional. In Iran, the majority of drug addicts are married men. Hence, this study focused on wives of drug addicts in Iran who were actively involved in Nar-Anon self-help groups. However, their experience in the journey to recovery from co-dependency is unclear. There is also a lack of consensual definition about the concept of co-dependency and its recovery process despite the vast use of this term in addiction counseling. This qualitative study explored the characteristics of co-dependency among wives of drug addicts in Iran before their involvement in NarAnon self-help groups and provided insight into the process of their recovery through participation in Nar-Anon. This study was guided by two research questions: 1) What are the characteristics of codependency among wives of drug addicts before their involvement in Nar-Anon self-help groups in Iran? 2) How do the wives of drug addicts recover from co-dependency based on their experiences in Nar-Anon self-help groups in Iran? Specifically, this study employed qualitative case study design. Based on purposive snowball sampling technique, 11 Iranian wives of drug addicts voluntarily participated. The respondents had been actively participating in Nar-Anon self-help groups and had completed working on the 12 steps of the Nar-Anon program. The data were collected through face to face interviews, non-participation observation, and documents. The data derived from transcripts of the interviews were analyzed through constant comparative method. Field notes, and documents were used to triangulate the data. The analyses of data derived from the first research question yielded five major themes for the characteristics of co-dependency among wives of Iranian drug addicts, namely: denial, enabling behaviors, low self-worth, enmeshed self, and weak relationship with God. The findings showed that the characteristics of co-dependency among wives of Iranian drug addicts were mostly similar to the characteristics of co-dependents in previous studies conducted outside Iran. However, the finding that “Weak relationship with God” as one of the characteristics of co-dependent wives in Iran, had rarely been reported in previous studies. Seven interconnected themes emerged from analyses based on the second research question including: social network of Nar-Anon, raised awareness, acceptance of the reality, spiritual growth, detachment from unhealthy dependence on others, taking the responsibility of herself, and transferring the message of Nar-Anon to others. The findings indicated that recovery from co-dependency was an ongoing process which takes place gradually through regular participation in the Nar-Anon self-help program and step work. The findings of this study demonstrated the importance of a supportive and empathetic group environment in the process of recovery from co-dependency. Furthermore, the present study highlighted the importance of integrating spirituality in the process of recovery from co-dependency. These findings of this study mainly support Whitefield’s Recovery Model of Co-dependency. In terms of practical implications, this study would help addiction counselors and other mental health professionals in Iran to gain a better understanding of the characteristics of co-dependency among wives of drug addicts and to provide more effective services to family members of drug addicts.